Existence of at least one positive continuing solution of Urysohn quadratic integral equation by Schauder fixed-point theorem. - Ben Saoud, Insaf; Makhzoum, Haitham; Msaik, Kheria (Libyan Journal of Science &Technology, 2022)
We employ Schauder fixed-point Theorem to prove the existence of at least one positive con-tinuous solution of the quadratic integral equation Moreover, the maximal and the minimal solutions of the last equation are also proved.